2011
DOI: 10.1007/s00468-011-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of seed size in modulating leaf physiology and early plant performance in two tree species

Abstract: The size of seeds and the microsite of seed dispersal may affect the early establishment of seedlings through different physiological processes. Here, we examined the effects of seed size and light availability on seedling growth and survival, and whether such effects were mediated by water use efficiency. Acorns of Quercus petraea and the more drought-tolerant Quercus pyrenaica were sowed within and around a tree canopy gap in a subMediterranean forest stand. We monitored seedling emergence and measured preda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Numerous studies have reported that bigger acorns lead to increased seedling growth, which can improve seedling performance by providing the resources to grow deep and extensive root systems, giving access to water from deep within the soil profile (Stock et al 1990, Triphati and Khan 1990, Osunkoja et al 1994, Gómez 2004, Ramírez-Valiente et al 2009Rodríguez-Calcerrada et al 2011). In fact, strong associations have been reported between acorn mass and survival in Q. ilex and Q. suber (Gómez 2004, Ramírez-Valiente et al 2009.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported that bigger acorns lead to increased seedling growth, which can improve seedling performance by providing the resources to grow deep and extensive root systems, giving access to water from deep within the soil profile (Stock et al 1990, Triphati and Khan 1990, Osunkoja et al 1994, Gómez 2004, Ramírez-Valiente et al 2009Rodríguez-Calcerrada et al 2011). In fact, strong associations have been reported between acorn mass and survival in Q. ilex and Q. suber (Gómez 2004, Ramírez-Valiente et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that root investment might be critical in allowing both Q. ilex and Q. suber to cope with water stress during prolonged droughts. In addition, seed mass is also considered a key trait determining the successful recruitment of seedlings, particularly in dry environments (Leishman and Westoby 1994, Seiwa 2000, Baraloto et al 2005, Rodríguez-Calcerrada et al 2011. The importance of seed mass lies in the influence that it exerts on traits such as above-and belowground growth during seedling establishment under both competitive and resourcelimiting conditions (Moles and Westoby 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Q. mongolica, the light demanding tree species, was characterized by particularly large seeds, which provided abundant energy reserves for initial seedling survival under light-shortage conditions (Geritz et al, 1999). The large acorns lead to taller seedlings with high carbohydrate reserves and nutrients, which facilitates seedling survival and growth under resource-limitation conditions (Ramírez-Valiente et al, 2009;Hallett et al, 2011;Rodríguez-Calcerrada et al, 2011).…”
Section: Across-species Comparison In Low Light and Suggestions For Nmentioning
confidence: 99%
“…Seed size is a central trait of plant ecology and evolution (Moles et al, 2005a;2005b), conditioning the probability of seed abundance and dispersal (Guo et al, 2000), predation, germination (Pearson et al, 2002), and seedling survival, even within a single species (Obeso et al, 2011). Additionally, evidence of early plant performance can be found by examining the distribution of seed size (Rodríguez-Calcerrada et al, 2011).…”
Section: Introductionmentioning
confidence: 99%